Snapdragons: i'm not wearing that! - Clarke, Jane; Mostyn, David (Oxford University Press UK, 2005)
Presents a collection of stories. Bookbanded for easy classroom management, this work contains Reading notes for parents/carers on the inside covers. Guided reading cards and teaching notes are also available.